CMTM3 Inhibits Human Testicular Cancer Cell Growth through Inducing Cell-Cycle Arrest and Apoptosis - Li, Zesong (Public Library of Science, 2014)
Human CMTM3 has been proposed as a putative tumor suppressor gene. The loss of CMTM3 has been found in several carcinomas. However, the regulation of CMTM3 expression and its function in tumor progression remain largely unknown. Here, we investigated the regulation of CMTM3 expression, function and molecular mechanism in human testicular cancer cells. CMTM3 was frequently downregulated or silenced in testicular cancer cell lines and tumor tissues but highly expressed in normal testis tissues. The re-expression of CMTM3 significantly suppressed the colony formation, proliferation, and migration capacity of testicular cancer cells by inducing a G2 cell cycle arrest and apoptosis. Moreover, the re-expression of CMTM3 activated the transcription of p53, induced p53 accumulation, up-regulated the expression of p21, and increased the cleavage of caspase 9, 8, 3, and PARP. The downregulation of CMTM3 in clinical tumor tissues was associated with the methylation of a single CpG site located within the Sp1/Sp3-responsive region of the core promoter. These results indicate that CMTM3 can function as tumor suppressor through the induction of a G2 cell cycle arrest and apoptosis. CMTM3 is thus involved in testicular cancer pathogenesis, and it is frequently at least partially silenced by the methylation of a single, specific CpG site in tumor tissues.